(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2013)
Representations of motherhood dominate the television landscape in a variety of popular genre texts, and as such it is important that we consider the ways in which these women are being constructed and circulated on the small screen. Indeed, although much work has been done to investigate the depiction of women on television, little research exists to account for the portrayal of mothering, motherhood, and the maternal role. With this in mind, this article introduces extant literature concerning the representation of motherhood in the media and then examines ways in which this research might be understood in relation to the depiction of mothers in soap opera, situation comedy, teen drama, dramedy and reality television. It considers the ways in which popular television texts form a consensus as they negotiate the idealized image of the ‘good’ mother in favour of a more attainable depiction of ‘good enough’ mothering which stands apart from the romanticized image of the ideal mother that dominates the broader entertainment arena.